Pseudoxanthoma Elasticum: Case Report - Gomes, Maria Fernanda (2017)
Pseudoxanthoma Elasticum (PXE) is a rare hereditary autosomal recessive disorder with a molecular defect in the ABCC6 gene. This dysfunction causes accumulation of calcium that causes degeneration of the elastic fibers, mainly in the eyes, cardiovascular system and skin. The case of a 61-year-old patient with PXE, with decreased visual acuity for 5 years and asymptomatic yellowish papules in the underarms and neck for 30 years is presented.